Foliar epidermal characteristics and preliminary phytochemistry of Ixora coccinea Linn, and ixora parviflora vahl. (1999)
Two ornamental species of ixora have been investigated morphologically and phytochemicaly. The leaves are oblong with acute apices and cordate bases In I. coccinea and elliptic with acuminate apices and obtuse bases In I. parviflora. The leaves are also larger in the latter. Epidermal cells are Isodlametric on the adaxial surfaces and irregular on the abaxial surfaces with curved anticlinal walls. Epidermal cells are larger In I parviflora. Paracytic stomata are found in both taxa while I. coccinea Is amphistomatic with the stomata on the adaxial surface restricted to areas around the midvein, I parviflora Is hypostomatic. A higher stomatal Index occurs In I. coccinea Trichomes which are restricted to the abaxial surfaces of the two taxa are simple, short, unicellular, peg-like or cone-like, and sometimes curved. Trichomes are, however, longer In I. parviflora Alkaloids, saponins and tannins are present in both taxa. Free or combined anthraqulnones and cardinc glycosides were not detectable in any of the species. An artificial key is present for the Identification of the two species.